Principles of aerosol jet printing. (5th July 2018) - Secor, Ethan B
Abstract: Aerosol jet printing (AJP) has emerged as a promising method for microscale digital additive manufacturing using functional nanomaterial inks. While compelling capabilities have been demonstrated in the research community in recent years, the development and refinement of inks and process parameters largely follows empirical observations, with an extensive phase space over which to optimize. While this has led to general qualitative guidelines and ink- and machine-specific correlations, a more fundamental understanding based on principles of aerosol physics and fluid mechanics is lacking. This contrasts with more mature printing technologies, for which foundational physical principles have been rigorously examined. Presented here is a broad framework for describing the AJP process. Simple analytical models are employed to ensure generality and accessibility of the results, while experimental validation using a silver nanoparticle ink supports the physical relevance of the approach. This basic understanding enables a description of process limitations grounded in fundamental principles, as well as guidelines for improved printer design, ink formulation, and print parameter optimization.